The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsmedchemlett.9b00402
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Study of Covalent Pan-phosphatidylinositol 5-Phosphate 4-Kinase Inhibitors

Abstract: Phosphatidylinositol 5-phosphate 4-kinases (PI5P4Ks) are important molecular players in a variety of diseases, such as cancer. Currently available PI5P4K inhibitors are reversible small molecules, which may lack selectivity and sufficient cellular on-target activity. In this study, we present a new class of covalent pan-PI5P4K inhibitors with potent biochemical and cellular activity. Our designs are based on THZ-P1-2, a covalent PI5P4K inhibitor previously developed in our lab. Here, we report further structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 17 publications
(21 reference statements)
1
32
0
Order By: Relevance
“…While this paper was under review, two new classes of chemical probes targeting PI5P4K were reported (62)(63)(64). Although these inhibitors appear to have weaker affinities than CC260 in vitro, one of them can react covalently with a free cysteine adjacent to the lipid kinase's active site, which should enhance its effectiveness and selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…While this paper was under review, two new classes of chemical probes targeting PI5P4K were reported (62)(63)(64). Although these inhibitors appear to have weaker affinities than CC260 in vitro, one of them can react covalently with a free cysteine adjacent to the lipid kinase's active site, which should enhance its effectiveness and selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…JNK-IN-7 was found to inhibit the kinase activity of PI5P4Ka/b/g in a radiometric thin-layer chromatography (TLC) assay (Figures S1B and S1C), and mass spectrometry revealed labeling of cysteine residues located on a disordered loop that is not observed in the available PI5P4K crystal structures (Figures S1D and S1E). We pursued a focused medicinal chemistry campaign guided by biochemical kinase assays and cellular pulldowns to optimize the potency and selectivity of phenylamino-pyrimidine, which resulted in the development of THZ-P1-2 (Figure 1A) (full structure-activity relationship study described in Manz et al, 2019). THZ-P1-2 demonstrated inhibition of PI5P4Ka kinase activity (Figure 1B), with a half maximal inhibitory concentration (IC 50 ) of 190 nM using an ADP-Glo (Promega) bioluminescence assay.…”
Section: Resultsmentioning
confidence: 99%
“…Originally inspired by the imatinib core structure, this ''privileged'' kinase scaffold served as a promising starting point for developing a selection of analogs with chemical modifications with which to explore structure-activity relationships. Among this panel of molecules (Manz et al, 2019), we found a critical feature resulting in superior potency to be a switch from a 2,4-pyrimidine to a 4,6-pyrimidine hinge-interacting motif. We established THZ-P1-2's inhibitory activity with an apparent IC 50 of 190 nM on PI5P4Ka in a fixed time point assay, the isoform with the highest kinase activity and thus easiest to analyze using an ATPase assay (ADP-Glo).…”
Section: Discussionmentioning
confidence: 99%
“…All things considered, in the recent past, PI5P4Ks and their product PI-4,5-P 2 have risen from insignificance to being without a doubt one of the key metabolic sensors and regulators within the cell as well as pivotal players for interorganelle communication necessary for cell survival. With drugs being developed against these kinases (Davis et al, 2013;Clarke et al, 2015;Al-Ramahi et al, 2017;Kitagawa et al, 2017;Manz et al, 2020;Sivakumaren et al, 2020;Chen et al, 2021), targeting them in the near future in various diseases is looking brighter.…”
Section: Health and Disease: Pi5p4ks Emerge As Exciting Targetsmentioning
confidence: 99%